E-GrabCut： an economic method of iterative video object extraction - DONG, Le; FENG, Ning; MAO, Mengdie; HE, Ling; WANG, Jingjing (Frontiers of Computer Science, 2017)
Efficient, interactive foreground/background segmentation in video is of great practical importance in video editing. This paper proposes an interactive and unsupervised video object segmentation algorithm named E-GrabCut concentrating on achieving both of the segmentation quality and time efficiency as highly demanded in the related filed. There are three features in the proposed algorithms. Firstly, we have developed a powerful, non-iterative version of the optimization process for each frame. Secondly, more user interaction in the first frame is used to improve the Gaussian Mixture Model (GMM). Thirdly, a robust algorithm for the following frame segmentation has been developed by reusing the previous GMM. Extensive experiments demonstrate that our method outperforms the state-of-the-art video segmentation algorithm in terms of integration of time efficiency and segmentation quality.